Canada : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
The Canadian economy bounced back strongly from the effects of the Asian financial crisis and the turmoil in world financial markets last year, reflecting a rebound in commodity prices, continued strong U.S. growth, and strengthening domestic demand, particularly investment spending. Executive Directors commended the authorities for maintaining sound macroeconomic and structural policies over most of the past decade, which had underpinned the strong performance of the Canadian economy, now in its eighth consecutive year of expansion, and welcomed Canada's participation in Financial System Stability Assessments.